(untitled) (Bangladesh Journal of Pharmacology, 2017)
The current study was aimed to investigate the extracts from Heliotropium strigosum and Trapa bicornis phytochemically for various constituents and pharmacologically for gastro-intestinal disorders. Phytochemical analysis indicated the presence of alkaloids, flavonoids, glycosides and tannins in both the extracts. In castor oil-induced diarrhea, H. strigosum and T. bicornis, at 100-1000 mg/kg dose provided protection of 10-83% and 14-76% respectively. In isolated rabbit jejunum preparations, T. bicornis (0.01-5 mg/mL) relaxed the spontaneous and K+ (80 mM)-induced contractions with EC50 values of 1.2 mg/mL and 2.6 mg/mL respectively, suggesting that spasmolytic effect was possibly mediated through calcium channel blockade. This was further authenticated when pretreatment of tissues with T. bicornis (1-5 mg/mL) caused rightward shift of Ca++ concentrationresponse curves, similar to verapamil. In acute toxicity test, both extracts were safe up to 10 g/kg dose. These results indicated the usefulness of H. strigosum and T. bicornis in the treatment of hyperactive gut disorders.